Mathematics Underground - Luther, Kenneth H. (PRIMUS : problems, resources, and issues in mathematics undergraduate studies, 2012)
Mathematical modeling of groundwater flow is a topic at the intersection of mathematics and geohydrology and is rarely encountered in undergraduate mathematics. However, this subject is full of interesting and meaningful examples of truly applied mathematics accessible to undergraduates, from the pre-calculus to advanced mathematics levels. This article shows four examples of increasing complexity which illustrate the possible uses of the subject in creating examples for different courses.